2011
DOI: 10.1371/journal.pntd.0001218
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Peak Shift in a Humoral Response to Helminths: Age Profiles of IgE in the Shuar of Ecuador, the Tsimane of Bolivia, and the U.S. NHANES

Abstract: BackgroundThe peak shift model predicts that the age-profile of a pathogen's prevalence depends upon its transmission rate, peaking earlier in populations with higher transmission and declining as partial immunity is acquired. Helminth infections are associated with increased immunoglobulin E (IgE), which may convey partial immunity and influence the peak shift. Although studies have noted peak shifts in helminths, corresponding peak shifts in total IgE have not been investigated, nor has the age-patterning be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 64 publications
(79 reference statements)
3
92
0
2
Order By: Relevance
“…THLHP researchers work extensively in Tsimane villages, collecting demographic, anthropological and biomedical data, while also providing primary medical care. Helminth infections are highly prevalent, infecting 57% of the population [19].…”
Section: Materials and Methods (A) Subject Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…THLHP researchers work extensively in Tsimane villages, collecting demographic, anthropological and biomedical data, while also providing primary medical care. Helminth infections are highly prevalent, infecting 57% of the population [19].…”
Section: Materials and Methods (A) Subject Populationmentioning
confidence: 99%
“…Following on-site analysis of participant blood and faecal samples, physicians administered vitamins, antibiotics, anti-protozans and anti-helminthics as warranted. Ethnographic and epidemiological information on the Tsimane, methods for age estimation, subject sampling, biomarker collection and physician diagnostics have been described elsewhere [19,20].…”
Section: (B) Data Collection and Medical Carementioning
confidence: 99%
See 1 more Smart Citation
“…In the high-SES school where the prevalence of T. trichiura was much lower, infection with this parasite was not significantly associated with the increased levels of total IgE, suggesting that levels of total IgE in low-SES school are likely to be the consequence of higher transmission of T. trichiura and other helminth such as A. lumbricoides which was also prevalent in low-SES school. In line with this, a study by Blackwell et al [37] showed that in rural Ecuador and Bolivia, total IgE increased with increasing helminth positivity and decreased in parallel with reduction of helminth infestation [38].…”
Section: Discussionmentioning
confidence: 62%
“…47 Additional risk factors could have been due to the very narrow genomic base of such isolated populations which would have produced a high level of human leukocyte antigen homogeneity through a founder effect or a Th2 bias created by exposure to a very limited set of pathogens such as helminths. [48][49][50] In dysentery, disruption of the stable enteric ecosystem by a single pathogen was magnified by the host response into a dysfunctional inflammatory reaction that presented as dysentery. Death was through a protein-losing enteropathy that further degraded the host's ability to respond to infections not unlike those seen in severely malnourished groups such as prisoners of war.…”
Section: Discussionmentioning
confidence: 99%